1985
DOI: 10.3758/bf03213367
|View full text |Cite
|
Sign up to set email alerts
|

Age dependency in neophobia: Its influence on taste-aversion learning and the flavor-preexposure effect in rats

Abstract: Five experiments were conducted to evaluate various aspects of stimulus preexposure effects on conditioned saccharin aversion in rats of three age groups: weanling (19-25 days), young-adult (92-170 days), and old-age (680-850 days). In Experiment 1, flavor neophobia was examined. Only the young-adult and old-age animals showed evidence of neophobia. Furthermore, habituation of the neophobic reaction differed for these two age groups. Using a brief to moderately long flavorpreexposure period and an intense US (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
2
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 13 publications
2
25
2
3
Order By: Relevance
“…Results of several studies have shown that it is more difficult to condition an aversion to taste in weanling rats than in adults and that conditioned taste aversion fails to occur in young rats with long CS-US intervals (Baker et al, 1977;Gregg , Kittrell , Domjan , & Arnsel, 1978;Martin & Timmins , 1980). Also, a recent study has shown that the ease with which an association is made between taste and an immediate illness is directly related to age in rats whose ages range from weanling to old age (Misanin et al, 1985). In another sense, the present results are surprising since previous work from our laboratory (Hinderliter & Misanin, 1988) suggested that aged rats would be more likely to show poorer long-delay learning than young adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of several studies have shown that it is more difficult to condition an aversion to taste in weanling rats than in adults and that conditioned taste aversion fails to occur in young rats with long CS-US intervals (Baker et al, 1977;Gregg , Kittrell , Domjan , & Arnsel, 1978;Martin & Timmins , 1980). Also, a recent study has shown that the ease with which an association is made between taste and an immediate illness is directly related to age in rats whose ages range from weanling to old age (Misanin et al, 1985). In another sense, the present results are surprising since previous work from our laboratory (Hinderliter & Misanin, 1988) suggested that aged rats would be more likely to show poorer long-delay learning than young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Ingram and Peacock's (1980) failure to find age differences may have been due to their relatively intense US . The results of a recent study (Misanin, Blatt, & Hinderliter, 1985) indicate that age differences in conditioned taste aversion may be obscured by a US of even moderate intensity. Furthermore, Hinderliter and Misanin (1988), using a weaker US (.15 M LiCl) than that used by Ingram and Peacock (.4 M LiCl), found that both weanling and aged rats showed substantially less aversion to a novel flavor than did young adults when the illnessinducing US was delayed 1 h after access to the flavor CS.…”
mentioning
confidence: 94%
“…While some studies show an increased intake of preexposed tastants in infant rats, that is, a reduction of neophobia (Gemberling, Domjan, & Amsel, 1980;Rudy, Vogt, & Hyson, 1984), in several others this effect is not observed (Chotro & Alonso, 1999;Hoffmann, Molina, Kucharski, & Spear, 1987;Misanin, Blatt, & Hinderliter, 1985;Rudy et al, 1984). In any case, it remains clear that the manifestation of neophobia increases with age (Misanin et al, 1985;Moron & Gallo, 2007;Rudy et al, 1984). The results of those studies in which no clear changes in intake were evidenced after taste exposure could be interpreted as maturational deficits, reflected either as a failure to perceive and discriminate between tastants, a failure to detect novelty/familiarity differences, or, perhaps, an inability to respond to them or to regulate intake.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that old-adult rats are less lrkely than w e a n h g or young-adult rats to attend to the conditioning context (a suspended galvanized rodent cage) because unWre weanlmgs and young adults they have spent many months in similar home cages (4,9). It has been suggested that old-adult rats are less lrkely than w e a n h g or young-adult rats to attend to the conditioning context (a suspended galvanized rodent cage) because unWre weanlmgs and young adults they have spent many months in similar home cages (4,9).…”
mentioning
confidence: 99%